Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00417-017-3777-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of retinal artery occlusion using transluminal Nd:YAG laser: a systematic review and meta-analysis

Abstract: TYE was followed by significant visual improvement in the vast majority of cases, including CRAO, and was frequently associated with vitreous hemorrhage. Patients with poor visual acuity appear to benefit further and higher pulse energies may be detrimental. Lack of randomization and intrinsic biases prevent any definite conclusions regarding the benefits and further research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Most of these reports are from case series, and a randomized control trial would be beneficial to conclude on the significance of Nd: YAG laser in the treatment of CRAO. [ 39 40 ] Pars plana vitrectomy Pars plana vitrectomy and removal of embolus have been reported in some cases and case series; however, the studies are limited and further randomized control studies are required to ensure the safety of this procedure. [ 41 42 ] IV and intra-arterial (IA) tissue plasminogen activator (tPA) TPA is a naturally occurring thrombolytic agent which is approved for use in patients with acute ischemic syndrome, pulmonary embolism, and acute myocardial infarction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these reports are from case series, and a randomized control trial would be beneficial to conclude on the significance of Nd: YAG laser in the treatment of CRAO. [ 39 40 ] Pars plana vitrectomy Pars plana vitrectomy and removal of embolus have been reported in some cases and case series; however, the studies are limited and further randomized control studies are required to ensure the safety of this procedure. [ 41 42 ] IV and intra-arterial (IA) tissue plasminogen activator (tPA) TPA is a naturally occurring thrombolytic agent which is approved for use in patients with acute ischemic syndrome, pulmonary embolism, and acute myocardial infarction.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these reports are from case series, and a randomized control trial would be beneficial to conclude on the significance of Nd: YAG laser in the treatment of CRAO. [ 39 40 ]…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Nd:YAG laser embolectomy has been performed within retinal vessels to dislodge emboli. A meta-analysis by Man et al30 of Nd:YAG laser embolectomy found a statistically significant improvement in VA with a weighted mean change from 20/252 to 20/47. Surprisingly, visual improvement was similar regardless of time to treatment varying from under 4 hrs up to 1 week.…”
Section: Discussionmentioning
confidence: 99%
“…Though the results of these studies showed improvement in retinal perfusion in the intervention groups, there was no improvement in vision 4Table 1A Summary of Current Conservative Treatment Options and Their Mechanism of Action 4,6,30Conservative Treatment Options for CRAOTreatment OptionPossible Mechanism of ActionSublingual isosorbide dinitrateDilation of retinal vasculature thus increased perfusion into the retinal arteryCarbogen inhalationInhalation of this mixture of 95% oxygen and 5% carbon dioxide to increase blood carbon dioxide concentration preventing oxygen-induced vasoconstriction thus allowing increased perfusion to retinal tissueHyperbaric oxygenInhalation of hyperbaric oxygen to increase oxygen tension and oxygen delivery to ischaemic retinal tissueOcular massageDigital compression of the globe to mechanically dislodge the embolus allowing it to pass through the retinal circulationAnterior chamber paracentesisWithdrawal of 0.1–0.2 mL of aqueous fluid to reduce intra-ocular pressure (IOP) and allow an increase in perfusion pressureIV acetazolamideIV infusion to reduce intra-ocular pressure (IOP) to allow an increase in perfusion pressureIV mannitolPentoxifyllineReduction of red blood cell rigidity allowing them to pass through capillaries with greater ease and a reduction of blood viscositySystemic steroidsReduction in vascular endothelial oedemaEnhanced external counter pulsationSequential inflation of pneumatic cuffs around the lower extremities at diastole to increase venous return and at the onset of systole to decrease systolic pressure causing increased blood flowNeodymium-doped yttrium aluminium garnet (Nd:YAG) laser embolectomyNd:YAG laser to dislodge embolus…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 There is no consensus regarding the timing and method of retinal artery treatment. 12 , 13 , 14 Our patient presented 72 hours after the onset of symptoms and considering his initial visual acuity, we administered pentoxifylline and dextran therapy with the aim of increasing retinal tissue oxygenation via vasodilatation and hemodilution. Anticoagulant and antiaggregant drugs were used because of the patient’s comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%